2024
DOI: 10.3390/app14020932
|View full text |Cite
|
Sign up to set email alerts
|

New Concept of Dual-Sinusoid Distributed Fiber-Optic Sensors Antiphase-Placed for the SHM of Smart Composite Structures for Offshore

Hao Su,
Monssef Drissi-Habti,
Valter Carvelli

Abstract: This work is a follow-up to previous research by our team and is devoted to studying a dual-sinusoidal placement of distributed fiber-optic sensors (FOSs) that are embedded inside an adhesive joint between two composite laminates. The constructed smart continuous fiber-reinforced polymer composite structure is well suited to the structural health monitoring (SHM) system for offshore wind turbine blades. Three main drawbacks of SHM through embedded distributed FOSs, however, have been identified in this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Their findings showed that the strain rate in the small contact area affects material properties such as hardness, yield strength, and fracture toughness, as well as the plastic deformation zone created by the scratching process. They also found that higher temperatures from faster scratching speeds reduced the radius of the plastic deformation zone, shortened crack lengths, decreased brittle fractures, and minimized subsurface damage [39].…”
Section: Fbg Sensorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Their findings showed that the strain rate in the small contact area affects material properties such as hardness, yield strength, and fracture toughness, as well as the plastic deformation zone created by the scratching process. They also found that higher temperatures from faster scratching speeds reduced the radius of the plastic deformation zone, shortened crack lengths, decreased brittle fractures, and minimized subsurface damage [39].…”
Section: Fbg Sensorsmentioning
confidence: 94%
“…Qu et al also explored diverse methodologies for monitoring the structural response of a carbon-fiber composite cylinder under internal pressure loading conditions, utilizing integrated optical fiber sensors [38]. Huan et al studied the subsurface damage in BK7 glass when scratched with a single abrasive, looking at how strain rate and temperature affect the material [39]. They wanted to see how these factors influence material properties, the size of the plastic deformation zone, and the start and growth of cracks such as lateral and median cracks.…”
Section: Fbg Sensorsmentioning
confidence: 99%
See 1 more Smart Citation